2016
DOI: 10.1111/jmft.12175
|View full text |Cite
|
Sign up to set email alerts
|

The Family System and Depressive Symptoms during the College Years: Triangulation, Parental Differential Treatment, and Sibling Warmth as Predictors

Abstract: Guided by Bowen theory, we investigated the relationships between parent-child triangulation, parental differential treatment (PDT), sibling warmth, and individual depressive symptoms in a sample of 77 sibling dyads, aged 18-25 years, recruited through undergraduate classes at a U.S. public University. Results of the actor-partner interdependence models suggested that being triangulated into parental conflict was positively related to both siblings' perception of PDT; however, as one sibling felt triangulated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
(65 reference statements)
0
19
1
1
Order By: Relevance
“…Although some evidence shows that differentiated parental treatment can have negative consequences on young people [20,21], this study shows that in young women the extreme hostility of the mother decreases the appreciation for life and stress management-On the other hand, these dimensions improve with the warmth of the mother. These results are very much in line with a study that found out that low parental warmth is associated with bulimic behaviour [27].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although some evidence shows that differentiated parental treatment can have negative consequences on young people [20,21], this study shows that in young women the extreme hostility of the mother decreases the appreciation for life and stress management-On the other hand, these dimensions improve with the warmth of the mother. These results are very much in line with a study that found out that low parental warmth is associated with bulimic behaviour [27].…”
Section: Discussioncontrasting
confidence: 54%
“…Although this association is observed when children are treated differently by both the father and the mother, said association is mediated by cultural socialization when the father treats differently [20]. for both siblings, the perception of differences in parenting diminishes the warmth between siblings, while higher warmth between siblings is associated with lower depressive symptoms [21].…”
mentioning
confidence: 89%
“…For example, a father may downplay his worry about symptoms in his EA offspring, in reaction to the mother’s degree of distress or worry. The mother may hold a more hyperattentive focus on her offspring’s symptoms, in reaction to the father’s downplaying of any concern (see also Ponappa, Bartle‐Haring, Holowacz, & Ferriby, 2017).…”
Section: Differentiation Of Selfmentioning
confidence: 99%
“…Depression was specifically associated with triangulation during childhood (e.g., Wang & Crane, 2001), adolescence (e.g., Buchanan et al, 1991, Buehler et al, 2009, Grych, Raynor, & Fosco, 2004), and youth (e.g., Ponappa, Bartle‐Haring, Holowacz, & Ferriby, 2017; Sabatelli & Anderson, 1991). Among other detrimental consequences, Krieg associated triangulation with children's increased self‐blame for their parents' spousal distress.…”
Section: The Systemic Paradigm: a Relational View Of Mental Health Pamentioning
confidence: 99%